2021
DOI: 10.1016/j.intimp.2021.107828
|View full text |Cite|
|
Sign up to set email alerts
|

Different T cell related immunological profiles in COVID-19 patients compared to healthy controls

Abstract: In various pathological conditions, cellular immunity plays an important role in immune responses. Among immune cells, T lymphocytes pdomote cellular and humoral responses as well as innate immunity. Therefore, careful investigation of these cells has a significant impact on accurate knowledge in COVID-19 disease pathogenesis. In current research, the frequency and function of various T lymphocytes involved in immune responses examined in SARS‐CoV-2 patients with various disease severity compared to normal sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 71 publications
4
12
2
Order By: Relevance
“…A work conducted by Salehi Khesht et al that studied the responses to SARS-CoV-2 with different immunological profiles of T-cells found a positive correlation between the severity of the disease and the Th1 response [57], which could contradict our results. However, Salehi Khesht et al did not carry out a phenotypic study of the lymphocytic population and their study also did not indicate at what point in time of the infection the immune profiles were evaluated (acute or convalescent), so it is not possible to assess whether they mediated a rapid action against the infection or if it occurred.…”
Section: Discussioncontrasting
confidence: 99%
“…A work conducted by Salehi Khesht et al that studied the responses to SARS-CoV-2 with different immunological profiles of T-cells found a positive correlation between the severity of the disease and the Th1 response [57], which could contradict our results. However, Salehi Khesht et al did not carry out a phenotypic study of the lymphocytic population and their study also did not indicate at what point in time of the infection the immune profiles were evaluated (acute or convalescent), so it is not possible to assess whether they mediated a rapid action against the infection or if it occurred.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study highlights the importance of a Th17-like decrease associated with COVID-19 severity. In contrast with previous studies that identified high levels of Th17 cells in the peripheral blood of patients infected with SARS-CoV-2 [ 4 , 55 , 56 ], our data revealed that the frequency of Th17-like cells in patients with severe COVID-19 was significantly lower than that in the HD ( Figure 5 ). In agreement with our data, De Biasi et al showed that patients with COVID-19 displayed a lower level of Th17 cells with CCR6+CD4+CD3+ and CCR6+CD161+CD4+CD3+ phenotypes [ 38 ], and Gutiérrez-Bautista J. et al demonstrated a persistently low frequency of markers associated with Th1, Th17, and Th1/Th17 memory-effector T cells compared to healthy donors [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, new findings confirm that high activation of Th17 cells and high signaling of IL-17 are significantly associated with severe COVID-19 (231,246). A recent study showed exhausted T cell profiles are associated with increased Th17 responses in COVID-19 patients with pneumonia (247). It has been reported that Th17 cells increase during the period 2 to 3 weeks post-symptom onset can predict a poor prognosis for COVID-19 complications.…”
Section: Th17 Cellssupporting
confidence: 53%